The Godson Processors： Its Research, Development, and Contributions - 胡伟武 高燕萍 陈天石 肖俊华 (Journal of computer science and technology, 2011)
The Godson project with an R＆D history of 10 years is an independent national program of China that aims at developing advanced microprocessor technologies based on fundamental research and commercialization of the chip technology. We will give a comprehensive presentation of the Godson project, including its history, technical roadmaps, and several unique technical merits.